Synchronised displaying of three adult male Wilson’s Bird-of-Paradise Cicinnurus respublica on Batanta Island, West Papua, and an undescribed display posture - Ford, Trevor; Barnes, Chris; Prativi, Shita; Noske, Richard A (KUKILA, 2012)
Wilson’s Bird-of-paradise Cicinnurus respublica is endemic to two islands of the Raja Ampat island group off the western tip of the Bird’s Head peninsula of the island of New Guinea. Due to its remote home, it is little known, and its courtship behaviour in the wild was not described until the 1990s. To attract females for mating, males create and maintain a clearing, known as a court, on the forest floor, where they display on perches. These displays are normally performed by solitary males, but in this paper we describe an instance of three adult males displaying simultaneously, with highly synchronised movements, in the presence of three female-plumaged birds. This cooperative display incorporated at least five postures, one of which has not been described to date, involving the bird ‘bowing’ to accentuate its yellow hind neck patch. Whilst cooperative displays have not been observed in the closest relatives of this species, the Magnificent and King Birds-of-paradise, they appear to occur regularly in the four species of parotias Parotia spp., albeit for much shorter periods of time.